2014
DOI: 10.1021/ja505589d
|View full text |Cite
|
Sign up to set email alerts
|

Energy Transfer on Demand: Photoswitch-Directed Behavior of Metal–Porphyrin Frameworks

Abstract: In this paper, a photochromic diarylethene-based derivative that is coordinatively immobilized within an extended porphyrin framework is shown to maintain its photoswitchable behavior and to direct the photophysical properties of the host. In particular, emission of a framework composed of bis(5-pyridyl-2-methyl-3-thienyl)cyclopentene (BPMTC) and tetrakis(4-carboxyphenyl)porphyrin (H4TCPP) ligands anchored by Zn(2+) ions can be altered as a function of incident light. We attribute the observed cyclic fluoresce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
138
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 205 publications
(142 citation statements)
references
References 38 publications
1
138
0
3
Order By: Relevance
“…As illustrated above, the reversible modulation of CO 2 sorption by photoirradiation is realized by the photoreactive flexible PCP. Our study not only clearly showed the correlation between photoisomerization efficiency and porous properties, which was not reported for pioneering works 22, 23 with a photomodulable CO 2 sorption, but also enables a material designed from the viewpoint of structural flexibility in a crystalline state. Our preliminary results in sorption experiments of PCP 1′ with other gases such as N 2 (Supplementary Fig.…”
Section: Resultssupporting
confidence: 58%
“…As illustrated above, the reversible modulation of CO 2 sorption by photoirradiation is realized by the photoreactive flexible PCP. Our study not only clearly showed the correlation between photoisomerization efficiency and porous properties, which was not reported for pioneering works 22, 23 with a photomodulable CO 2 sorption, but also enables a material designed from the viewpoint of structural flexibility in a crystalline state. Our preliminary results in sorption experiments of PCP 1′ with other gases such as N 2 (Supplementary Fig.…”
Section: Resultssupporting
confidence: 58%
“…[1][2][3] Recently, a great deal of interest has been spent on incorporating photoactive ligands as guest molecules in MOFs for potential photovoltaic and photocatalytic applications. [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] For example, a series of Re(II), Ir(III), and Ru(II) metal 5,5′-dicarboxy-2,2′-bipyridine, DCBPY, coordination complexes have been incorporated into the Zr(IV) 4,4'-biphenyldicarboxylic acid, BPDC, MOF UiO-67 for the purpose of carbon dioxide reduction, water oxidation, and organic conversion reactions. 11 The UiO-67 MOF is comprised of Zr 6 (µ 3 -O) 4 (µ 3 -OH) 4 metal nodes connected by twelve BPDC ligand resulting in two distinct cavity-types: a tetrahedral cavity having a diameter of approximately 12 Å, and an octahedral cavity approximately 23 Å in diameter.…”
Section: Introductionmentioning
confidence: 99%
“…Light responsive MOFs, whose chemical and structural changes can be controlled merely by mild condition-light irradiation, have shown intriguing properties, and thus recently received great interest. [17][18][19][20][21][22][23][24][25][26][27][28] For example, light can induce configuration transformations of the linkers/guests, thus to tune the pores of MOFs and enhance their gas separation performances. [18][19][20][21] Photochemical reactions can also provide an alternative way to introduce functional groups/moieties and thus to develop smart MOFs with switchable optical absorption and fluorescence properties.…”
mentioning
confidence: 99%
“…[18][19][20][21] Photochemical reactions can also provide an alternative way to introduce functional groups/moieties and thus to develop smart MOFs with switchable optical absorption and fluorescence properties. [21][22][23][24][25] Because the light triggers the reactions in a one-photon process in these examined systems, we were not able to develop their spatial selectivity: the photochemical responses take place either on the surfaces or in the whole crystals of MOFs. It is essential to engineer the properties of MOFs using the light or laser in 3-dimensional (3D) structure, which would create functional patterns inside the MOF crystals and find applications in chemical sensors, optical switches, data storage and circuits.…”
mentioning
confidence: 99%